Cyber security and open government in Malaysia: issues and development - Zulhuda, Sonny (2016)
Open government is the notion that allows transparency of governments in running matters pertinent to public interests. According to that concept, the government shall allow its citizens an access to government documents and right to obtaining information relating to public matters. In this digital age, not only it is necessary to preserve the right to freedom of information for individuals, it is also critical to ensure that such freedom can be enhanced using the digital platform and information infrastructure. With this background, the question of how Government deals with information security challenges ranging from personal data to the government data is worth examining. This presentation is looking at the recent developments in Malaysia relating to the challenges of personal data protection and critical infrastructure protection and what policies and laws that are put in place. Lessons from cases and incidents surrounding information security and personal data breaches will be discussed to trigger discussions on relevant solutions and best practice.